Strategies to improve the maternal health programmes under NHM towards MDG-5: maternal mortality in Karnataka - Kularni, R. R.; Venkatesh, D (International Journal Of Community Medicine And Public Health, 2017)
Background: Since from the inception of safe mother hood programs in India during 1982-1990, there is no enough maternal health initiative and financial resource for funding public health activities. So number of maternal deaths is more in India, presently which is accounted 20% of the world total maternal deaths. The global and national importance has been given during 1990 by forming millennium development goal -5 (MDG) to improve maternal health programs. During these days MMR was high and there has been recognition for Maternal Health Programs since from 1997, when RCH-I, in the year 2005. National rural health mission (NRHM) was launched with the primary and main objective was to reduce infant and maternal mortality rate as per goal and target fixed by the 12th five year plan (NHM) and MDG -5. Under NHM enough financial resources envelop has been allotted to states of India as per program implementation plan (PIP), so effective utilization of these strategic and financial resources to reduce MMR. Hence this study needs to form strategies to improve the maternal health programs to reduce maternal mortality ratio as per NHM and MDG. Methods: We used the range of methods, like analytical methods to generate the strategies to reduce maternal deaths due to the particular cause by introducing the maternal health programmes with the strategies. Results: Maternal mortality ratio reduced from an estimated level of 437 in 1990 to 178 in 2010–12.The all India and Karnataka target for 2015 was 109 so far not reached. It has to be reached at least by 2017. Conclusions: Optimal using of resources with the implementation of proper strategies, it will give the exact result for achievement of planned goal. This study is also revealed that all the aspects of maternal health programmes and MMR.